2008
DOI: 10.1037/1528-3542.8.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Prepared for the worst: Readiness to acquire threat bias and susceptibility to elevate trait anxiety.

Abstract: Although people differ in their susceptibility to elevate trait anxiety in response to extended stress, little is known about the cognitive substrate of this particular individual difference. We report three studies designed to evaluate the hypothesis that individual differences in readiness to acquire an attentional bias toward threat cues, in response to a contingency that makes the acquisition of such a bias adaptive, underlie individual differences in susceptibility to elevate trait anxiety in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 53 publications
7
76
2
4
Order By: Relevance
“…Analogous to studies indicating that such individual differences predict changes in anxiety (Clarke et al, 2012;Clarke et al, 2008), we tested whether individual differences the natural propensity to attend to emotional material (i.e., pre-training attention bias scores) and the propensity to modify the natural attentional pattern (i.e., individual bias acquisition scores) were related to individual differences in performance on the transfer tasks. We found no evidence for transfer of attention training at the individual differences level of analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analogous to studies indicating that such individual differences predict changes in anxiety (Clarke et al, 2012;Clarke et al, 2008), we tested whether individual differences the natural propensity to attend to emotional material (i.e., pre-training attention bias scores) and the propensity to modify the natural attentional pattern (i.e., individual bias acquisition scores) were related to individual differences in performance on the transfer tasks. We found no evidence for transfer of attention training at the individual differences level of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Clark and colleagues, we computed an individual bias acquisition index by subtracting the pre-training from the posttraining attention bias score (Clarke et al, 2012;Clarke et al, 2008). For the affective taskswitching task, repetition and switch trials were identified, and switch costs were calculated by subtracting RTs on repetition trials from RTs on switch trials for the consistent and inconsistent block.…”
Section: Data Preparation and Analytical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Given that prior research has revealed marked individual differences in the malleability of attention bias through training (Clarke, Chen, & Guastella, 2012;Clarke, Macleod, & Shirazee, 2008; and that there also was substantial variability in attention bias scores both in the attentional control training and in the dot-probe task in the current study (see Table 1 Further analyses were conducted to establish whether the manipulations introduced in the training condition during the modification phase would also lead to a faster performance on the task (i.e., faster times to unscramble sentences at the modification phase in comparison to the baseline phase in the training condition). A 2 (Condition: Training, Control) x 2 (Phase: Baseline, Modification) mixed-design ANOVA with the mean time to unscramble the sentences as dependent variable showed a marginally significant Condition by Phase interaction, F(1,32)=3.35, p=.07,  2 =.09.…”
Section: Transfer Of Trainingmentioning
confidence: 99%
“…Prior research has revealed marked individual differences in the malleability of attention mechanisms through training (Clarke, Chen, & Guastella, 2012;Clarke, Macleod, & Shirazee, 2008;Everaert et al, 2014). Therefore, as in , individual differences in attention regulation implementation were indexed via residualized change scores (Segal et al, 2006).…”
Section: Analytic Planmentioning
confidence: 99%